Buletin Peternakan : KARAKTERISTIK KUANTITATIF DAN KUALITATIF KAMBING DAN DOMBA SEBAGAI HEWAN QURBAN DI MITRA TANI FARM - Komariah, Dwi Joko Setyono, Aslimah (Peternakan UGM, 2015)
The objective of the present study was to study the qualitative characteristics (wool color, horned) and the quantitative characteristics (body weight, chest circumference, body length, age) of sheep and goats for qurban in the Mitra Tani Farm; and the consumers preferences of choosing the sheep and goat required for ‘qurban’ event. In total eighty three Jawarandu goats; 16 Garut; 37 Thin-Tailed and 35 Fat-Tailed rams were observed to measure their body weight, chest circumference, body length, age, the present of horn and hair color